An Analysis of Writing Tasks in “Pathway to English” Textbook for Twelfth Grade of SMAN 5 Kota Jambi - Debora Novita Sari; Wennyta Wennyta; Efa Silfia (JELT: Journal of English Language Teaching, 2021)
This research was aimed to find out whether the writing task in “Pathway to English” textbook appropriate with the criteria of writing task as suggested by Paul Nation, in Nation’s theory. There are four kinds of tasks that suggested. Each of tasks has the following type : (1) Experienced Task (linked skills, draw and write, ten perfect sentences, partial writing, setting your own questions), (2) Shared Task (reproduction exercise/dicto-gloss, blackboard composition, group-class composition, writing with a secretary), (3) Guided Task (translation, picture composition, delayed copying, writing with grammar help, answer the questions, correction, complete the sentences, back writing, put the words in order, follow the model, what is it?, change the sentences, join the sentences, writing by steps, marking guided writing), (4) Independent Task. The method of this research was descriptive qualitative. To analyzed the data, the researcher used qualitative content analysis method. Research findings there are 54 types of writing task: 2 Experience task (1 Partial Writing, 1 Setting your own question), 1 Shared task ( 5 group class composition), 8 Guided task (1 translation, 7 look and write, 1 picture composition, 7 writing with grammar help, 10 answer the question, 4 correction, 11 complete the sentences, 2 put the words in order, 1 Independent task (6 independent).  The result of this research was that there are criteria are found that match with the criteria as suggested by Paul Nation, this proves that this book is appropriate with the criteria as suggested by Paul Nation.Key Words: Writing Task, English Textbook, Task Analysis